Analysis of the Interpretation Nafs Verses in the Qur'an and Its Relevance to the FOMO Phenomenon - Muhamad Ulil Albab; Abdul Fatah (al-Afkar, Journal For Islamic Studies, 2026)
Fear of Missing Out (FOMO) is a term referring to the anxiety or worry individuals feel about missing out on information, experiences, or events happening elsewhere. Factors contributing to FOMO include the ease of access to information, especially through social media. While social media, with all its features, greatly assists human work, this is only true if accompanied by effective self-regulation. Conversely, abundant information can negatively impact a person's psychological stability. This study aims to analyze the ulama's interpretation of the nafs verses (Ammārah, Lawwāmah, and Muṭma’innah) as a basis for understanding the dynamics of the human soul. These three verses were selected because commentators explicitly cite them as crucial categories in discussions of the human psyche. The research analysis was conducted in three stages: (1) exploring scholars' interpretations of the nafs verses; (2) mapping FOMO symptoms based on modern psychological literature; and (3) integrating the two to find common ground specifically, how the nafs verses can explain the FOMO phenomenon and simultaneously offer a Qur'anic solution. The findings show that the nafs concept in the Qur'an is highly relevant to the FOMO phenomenon, particularly in explaining impulsive urges, self-reflection, and inner peace as strategies for coping with digital anxiety.